Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης για τον τρόπο κατασκευής οροφής της Δημοτικής Αποθήκης
Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης για τον τρόπο κατασκευής οροφής της Δημοτικής Αποθήκης